If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = w Solving 18 = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 18 + -1w = w + -1w Combine like terms: w + -1w = 0 18 + -1w = 0 Add '-18' to each side of the equation. 18 + -18 + -1w = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1w = 0 + -18 -1w = 0 + -18 Combine like terms: 0 + -18 = -18 -1w = -18 Divide each side by '-1'. w = 18 Simplifying w = 18
| 18x^2-12x^3+3=0 | | G(-3)=3-27-3 | | 8^1/4-5^2/3 | | 84=4(1-4g) | | (b^4)^1/9=dsqrt(b^4) | | 2x+1.4=5.6 | | -1.2=1.8-3y | | 18=w/0.2 | | -9m-9=102 | | 587=8x+387 | | -2.8=5.2-2y | | -(-8x+4)+9x= | | -25=5(y-4) | | 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 |